Biddle Speech Dropped on Italy (1942)
New York Times article reporting that 600,000 copies of Francis Biddle's (1886-1968) Columbus Day address, which announced Italian immigrants are no longer classified as enemy aliens to the United States, were distributed in Italy.
Keywords: Biddle, Francis, 1886-1968; World War (1939-1945); Italy; Propaganda; Noncitizens